2009
DOI: 10.1007/s10803-009-0753-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Social Impairment and ASD Diagnosis in Younger Siblings of Children with Autism Spectrum Disorder

Abstract: Later-born siblings of children with autism spectrum disorder (Sibs-ASD) are at elevated risk for social impairments. Two putative predictors of later social impairment—measures of responding to joint attention and weighted triadic communication—were examined in a sample of 43 Sibs-ASD who were followed from 15 to 34 months of age. Results revealed that initial level of responding to joint attention and growth rate of weighted triadic communication predicted the degree of social impairment at the final measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
3
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(107 citation statements)
references
References 40 publications
4
92
3
5
Order By: Relevance
“…: Red flags differentiating ASD from TD but not DD were lack of response to contextual cues, lack of pointing, lack of vocalizations with consonants, and lack of playing with a variety of toys conventionally. 43 Other studies have assessed the use of gestures more generally. During the second year of life, a lower frequency of gesture use differentiated children with ASD from typically developing children 35,63 and from children with other developmental disorders.…”
Section: Statementmentioning
confidence: 99%
“…: Red flags differentiating ASD from TD but not DD were lack of response to contextual cues, lack of pointing, lack of vocalizations with consonants, and lack of playing with a variety of toys conventionally. 43 Other studies have assessed the use of gestures more generally. During the second year of life, a lower frequency of gesture use differentiated children with ASD from typically developing children 35,63 and from children with other developmental disorders.…”
Section: Statementmentioning
confidence: 99%
“…These works involve video clips of people engaged in social interaction [24] or images of human faces [38,39]; typical tasks are the study of the fixation patterns and the evaluation of the capacity of people with autism to recognize different emotions [40,41]. Other works have investigated the attentional bias for people with autism to follow others' gaze/head-turn direction [42], since several studies suggested that the ability to follow the gaze of another person is impaired in the case of autism [43,44].…”
Section: Main Contributions and Related Workmentioning
confidence: 99%
“…Con todo, es habitual encontrar una gran variabilidad de puntuaciones en los distintos grupos en esta edad, la cual hay que tener en cuenta para las evaluaciones. En las tareas de evaluación de RJA con acumulación de pistas, por ejemplo-sólo Mirar+Girar la cabeza, o Mirar+Girar la cabeza+Señalar con el dedo-los H-TEA pueden llegar a tener igual rendimiento que los H-DT (Rozga et al, 2011;Sullivan et al, 2007;Thorup et al 2016;Yoder, Stone, Walden & Malesa, 2009). En conclusión, las mediciones de frecuencia son insuficientes a los 6 meses (Rozga et al, 2011), y una tarea simple sin acumulación de pistas para la evaluación de la RJA resulta poco discriminatoria.…”
Section: Atención Conjuntaunclassified